Academic Factors Influencing Students Career Choices in the IT Field: Insights from South African IT Students - Ndovela, Sithembile; Mutanga, Bethel (Indonesian Journal of Information Systems, 2024)
Effective career decision-making is pivotal for students, influencing their prospects and employability. This study delves into the nuanced relationship between academic factors and career choices among Information Technology (IT) students. While existing literature acknowledges the broad impact of academic performance on career decisions, limited research explores this dynamic within the context of South African universities. This research employs a comprehensive mixed-methods approach, examining the influence of educational experience, mentorship, access to resources, and institutional support on students' academic performance and subsequent career choices. Through statistical analysis and qualitative interviews, the study unveils unique insights into the interconnected effects of these factors on IT career pursuits. The findings bear significance for educators, career counselors, policymakers, and industry stakeholders. By understanding the multifaceted elements shaping academic performance and career decisions, institutions can tailor support programs, refine curricula, and nurture holistic student development. Employers stand to gain insights into the attributes of high-performing individuals, aiding talent management and recruitment. For IT students, this research provides a profound exploration of the intricate links between academic performance, career choices, and outcomes, contributing to the broader discourse on workforce development and the future of the IT sector.